2000
DOI: 10.1034/j.1399-6576.2000.440324.x
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane as a sole anaesthetic for thymectomy in myasthenia gravis

Abstract: Myasthenia gravis is a challenging situation for anaesthesiologists due to its neuromuscular involvement. The main concerns are respiratory muscle weakness and side effects due to a heavy dose of anticholinesterases. This limits the use of sedatives, hypnotics and muscle relaxants. Inhalational anaesthetics are best suited. We describe our experience with sevoflurane as a sole anaesthetic in a child having juvenile-type myasthenia gravis with thymoma, who underwent thymectomy by midsternal incision. Very smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 9 publications
1
26
0
3
Order By: Relevance
“…The standards developed on the basis of in-house studies are in accordance with the suggestions of many authors, whose research indicates that myasthenia patients are more sensitive to the "relaxing" effect of inhaled agents [15,16].…”
Section: Tab I Demographic Datamentioning
confidence: 74%
“…The standards developed on the basis of in-house studies are in accordance with the suggestions of many authors, whose research indicates that myasthenia patients are more sensitive to the "relaxing" effect of inhaled agents [15,16].…”
Section: Tab I Demographic Datamentioning
confidence: 74%
“…However, consensus regarding the superiority of a specific technique has not been established [1,[6][7][8][9]. Itoh and Shibata [12] reported that the effect of propofol on the neuromuscular junction was less than the effect of sevoflurane in the same patient who underwent two separate anesthetic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic techniques, including intubation without a muscle relaxant, TIVA, or sevoflurane administration alone, have been used in transsternal thymectomy [1,[6][7][8][9]. Most patients with MG require thymectomy for the control and treatment of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding muscle relaxants in patients with myasthenia gravis can potentially lower the risk of postoperative muscle weakness and respiratory insufficiency thus leading to faster patient's recovery [9][10][11][12]. Other possible advantages of thoracic epidural anaesthesia include better patients' satisfaction, reduced hospital length of stay, and improved resource utilization.…”
Section: Introductionmentioning
confidence: 99%